2021
DOI: 10.4103/ijcm.ijcm_325_20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 12 weeks of yoga training on neurocognitive variables: A quasi-experimental study

Abstract: Background: Neurocognitive abilities are the brain-mind skills needed to initiate any task from the simplest to the most complex, decreases with advancing age. Attention, alertness, and memory are the basic neurocognitive functions most affected by age. There are potential benefits of yoga on neurocognitive functions because this ancient Indian technique positively nurtures the mind-body systems. Aim of the Study: The present study was aimed to evaluate the effect of 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…The anxiety levels also dipped among the children following the breath awareness practice. Continuous practice of Yoga for twelve weeks leads to signi cant improvement in short-term memory, attention, and alertness (Mondal & Deepeswar Singh, 2021). The fundamental neurocognitive processes that are most impacted by aging include attention, alertness, and memory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anxiety levels also dipped among the children following the breath awareness practice. Continuous practice of Yoga for twelve weeks leads to signi cant improvement in short-term memory, attention, and alertness (Mondal & Deepeswar Singh, 2021). The fundamental neurocognitive processes that are most impacted by aging include attention, alertness, and memory.…”
Section: Discussionmentioning
confidence: 99%
“…Changes were seen in theta and alpha powers in the frontal area of EEG during zen meditation in undergraduate students. High alpha power is a marker for a less active brain [29], which may be attributed to a more calm and positive brain state to facilitate meditation practice. Lower frequency EEH bands (alpha and theta) revealed high band power in Rajyoga meditators as compared to controls (Sharma & Chandra, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Chatterjee et al . [ 53 ] recorded improvement in T4, T4, and TSH level following yoga therapy; similarly, Chatterjee et al . [ 54 ] observed improvement in GH (growth hormone) and dehydroepiandrosterone sulfate (DHEAS) level following yoga therapy.…”
Section: Discussionmentioning
confidence: 84%
“…However, yogic practices such as the Sarvangasana increases the protein bound serum iodine and improves function of the thyroid gland. [ 53 55 ] Streeter et al . [ 56 ] noted a sharp increase in GABA following an hour of yoga practice, as shown by magnetic resonance spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…The yoga schedule is comprised of S urya namaskar , other A sanas , and P ranayama [ 39 ]. Recent research studies have reported promising effects of the yogic intervention on neurocognitive abilities promoting successful aging [ 40 ]. Several studies highlight that yoga could be a low-cost preventive measure for type 2 Diabetes Mellitus [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%